Association between transfusion of whole blood and recurrence of cancer. Issue 6546 (30th August 1986) - Blumberg, N; Heal, J M; Murphy, P; Agarwal, M M; Chuang, C
Abstract : Transfusion affects the immune response to renal transplantation and may be associated with recurrence of various human neoplasms. Data from patients with colonic, rectal, cervical, and prostate tumours showed an association between transfusion of any amount of whole blood or larger amounts of red blood cells at the time of surgery and later recurrence of cancer. Recipients of one unit of whole blood had a significantly higher incidence of recurrence (45%) than recipients of a single unit of red cells (12%) (p = 0.03). Recipients of two units of whole blood also had a higher rate of recurrence (52%) than those receiving two units of red cells (23%) (p = 0.03). Recipients of any amount of whole blood had similar recurrence rates (38-52%). Recipients of four or more units of red blood cells had a higher rate of recurrence (55%) than those receiving three or fewer units of red blood cells (20%) (p = 0.005). Mortality due to cancer in patients receiving three or fewer units of red blood cells (2%) was similar to that in patients who did not have transfusions (7%) and significantly lower than that observed in patients receiving three or fewer units of whole blood (20%) (p = 0.003). A proportional hazards risk analysis showed that transfusion of any whole blood or more than three units of red blood cells was significantly associated with earlier recurrence and death due to cancer. These data support an association between transfusion and recurrence of cancer. They also suggest that some factor present in greater amounts in whole blood, such as plasma, may contribute to the increased risk of recurrence in patients who have undergone transfusion. Until the questions raised by retrospective studies of cancer recurrence and transfusion can be answered by prospective interventional trials with washed red blood cells, red blood cells should be transfused to patients with cancer in preference to whole blood when clinically feasible.